Behaviors of Redox-Sensitive Components in the Volcanic Plume at Masaya Volcano, Nicaragua: H2 Oxidation and CO Preservation in Air - Kazahaya, Ryunosuke; Varnam, Matthew; Esse, Ben; Burton, Mike; Shinohara, Hiroshi; Ibarra, Martha (Frontiers in Earth Science, 2022)
Multi-disciplinary volcanic gas observations, including FTIR, Multi-GAS, and Alkali filter pack, were made at Masaya volcano, Nicaragua, in January 2018. During the observation period a lava lake was present, and the majority of the volcanic gases were likely emitted directly from the lava. The fractions of major components showed good consistency with previous studies, however we found the fraction of combustible components (such as H2) were lower than expected. The RH (log(H2/H2O)) value was measured to be less than -6, compared to the equilibrium RH value calculated to be around -3 from the iron speciation. The equilibrium calculations suggest oxidation of the volcanic gases by high-temperature mixing with the air once they are emitted from the lava lake, lowering the H2 content of the plume. In contrast to H2, a small amount of CO, another combustible species, was detected and the derived CO2/CO ratio of ca. 1000 is consistent with the equilibrium magmatic value. This indicates that CO is kinetically inert compared to H2. Our findings suggest that volcanic gases in the Masaya plume do not preserve information from when the gases were in equilibrium with the surrounding magma.